Life on a Neolithic site : Bylany - situational analysis of artefacts = Život na sidlišti kultury s linearni keramikou v Bylanech u Kutne Hory : situačni analyza artefaktu - Pavlu, Ivan (Institute of Archaeology, Czech Academy of Sciences, 2000)
Sažetak na češkom